1977
DOI: 10.1071/pp9770403
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Growth, Phosphate Content and Nitrogen Fixation in Mycorrhizal and Non-Mycorrhizal Medicago sativa

Abstract: Nodulated Medicago sativa cv. Europe plants, both non-mycorrhizal and mycorrhizal (inoculated with Glomus mosseae), were grown in sand or soil with a range of phosphate levels. The following parameters were measured: intensity of mycorrhizal infection, intensity of nodulation, growth, phosphate content, nitrogenase activity (acetylene reduction) and nitrogen content. Both nodulation and mycorrhizal infection had occurred within 2 weeks of inoculation with the appropriate endophytes. Major increases in dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…The mycorrhizal effects are of greater significance in soils of low nitrifying capacity in which uptake of the ammonium ion predominates (Carrodus, 1966;France & Reid, 1978;Raven et al, 1978;Ames et al, 1983). Daft & El-Giahmi (1974) and Smith & Daft (1977), have reported marked increases in nodulation, nitrogen fixation and growth with mycorrhizal inoculation of legumes. Ames et al (1983) have shown that mycorrhizal roots can also derive more nitrogen from an organic source than can non-mycorrhizal plants.…”
Section: Mycorrhizal Inoculation and Varying Degrees Of Root Interactmentioning
confidence: 99%
“…The mycorrhizal effects are of greater significance in soils of low nitrifying capacity in which uptake of the ammonium ion predominates (Carrodus, 1966;France & Reid, 1978;Raven et al, 1978;Ames et al, 1983). Daft & El-Giahmi (1974) and Smith & Daft (1977), have reported marked increases in nodulation, nitrogen fixation and growth with mycorrhizal inoculation of legumes. Ames et al (1983) have shown that mycorrhizal roots can also derive more nitrogen from an organic source than can non-mycorrhizal plants.…”
Section: Mycorrhizal Inoculation and Varying Degrees Of Root Interactmentioning
confidence: 99%
“…Furthermore, 0028-646X/81/060299-hll S02.00/0 ® 1981 The New Phytologist the method used to reintroduce mycorrhizal fungi poses new problems, not the least being the quantity and form of inoculum to add in order to give a level comparable to that in the original soil. In our studies of the effects of early endomycorrhizal infection on nodulation and growth of Trifolium subterraneum L. (Smith, Nicholas and Smith, 1979) we compared plants grown in sterilized and non-sterilized soil, and it has been suggested (e.g. by referees) that this approach is invalid.…”
Section: Introductionmentioning
confidence: 99%
“…There have been claims of direct effects of mycorrhizas on nodulation and nitrogen fixation in legumes (Mosse 1977;Powell & Sithamparanathan 1977;Smith & Daft 1977;Munns & Mosse 1980). However, Robson et al (1981) suggest that the effects of mycorrhizal infection on nodulation and N fixation in subterranean clover are indirect, and result from the improved P uptake and plant growth which follow from mycorrhiza development.…”
Section: Introductionmentioning
confidence: 99%